Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)